Compression profile of sport compression stockings in runners - Oficial, F. J.; Aparicio, I.; Julián, I.; Pérez- Soriano, P. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this study was to determine the interface pressure applied using two compressive stockings: medium compression (MC) and strong compression (SC); in three conditions: before, during and after running test. Ten male runners (n=10) exerted two laboratory test condition in different days: a) without compression stockings and b) with one kind of compression in each leg. Interface pressure was registered using PicoPress® device. In both compression conditions, the interface pressure was higher in proximal than distal sensors (MC p<0,05; SC p<0,001). Similar results were taken in dynamic condition, and lower level compression was observed after running test. In conclusion, compressive forces were higher in proximal compared to distal leg area. This is contradictory to the gradual decreasing compression principle.